Room-temperature ferromagnetism in boron-doped oxides: a combined first-principle and experimental study. (2nd April 2020) - Luitel, Homnath; Roy, Sujata; Chakrabarti, Mahuya; Chettri, P.; Tiwari, A.; Naik, V.; Sanyal, D.
ABSTRACT: The ferromagnetic properties of boron-doped oxides, namely ZnO, MgO, CdO and TiO2 have been studied using first-principle calculations based on density functional theory. A boron atom, when doped at an anion site, generates a magnetic moment per dopant atom ranging from ∼1 µB in TiO2 to ∼3 µB in ZnO. The source of magnetism in the boron-doped oxides is the 2p-orbital electrons of the dopant atom plus a small contribution coming from the oxygen atoms surrounding the dopant. A spin–spin interaction study reveals that the doping of B at O sites favours ferromagnetic spin coupling in ZnO, MgO, CdO and TiO2 . Boron-doped samples have been prepared by ion-beam irradiation with a 10 keV B + beam implanting on sample pallets. Magnetic measurements have been carried out for B + -ion-implanted oxide samples using a SQUID magnetometer. A stable room-temperature ferromagnetic ordering is observed in boron-ion-irradiated ZnO, MgO, CdO and TiO2 samples.